2004
DOI: 10.3354/meps284117
|View full text |Cite
|
Sign up to set email alerts
|

Emergence stress and morphological constraints affect the species distribution and growth of subtropical intertidal seagrasses

Abstract: The effects of emergence stress and morphological constraints on the distribution and growth of 3 subtropical seagrass species, Cymodocea rotundata, C. serrulata and Thalassia hemprichii, were examined in a series of transplantation experiments and a laboratory desiccation experiment. C. rotundata and T. hemprichii occur in both the intertidal and subtidal zones off Ishigaki Island, southwest Japan, whereas C. serrulata is found only in the subtidal zone. Within the same species, intertidal shoots for both C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 20 publications
0
27
0
5
Order By: Relevance
“…This is also true at coral reef coasts, which have shallow, intertidal reef flats created by reef-building organisms (e.g., corals, calcareous algae, and foraminifera) and calcareous sand distributions on beaches and reef islands (Woodroffe, 2002). Previous studies have shown distinct zonal distributions of reef-dwelling organisms due to subaerial exposure, which is basically a function of surface morphology in intertidal areas (e.g., Stoddart, 1969;Yamano et al, 2001;Tanaka and Nakaoka, 2004). However, possible future rises in sea levels threaten to drown or inundate coral reefs and islands (Leatherman, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…This is also true at coral reef coasts, which have shallow, intertidal reef flats created by reef-building organisms (e.g., corals, calcareous algae, and foraminifera) and calcareous sand distributions on beaches and reef islands (Woodroffe, 2002). Previous studies have shown distinct zonal distributions of reef-dwelling organisms due to subaerial exposure, which is basically a function of surface morphology in intertidal areas (e.g., Stoddart, 1969;Yamano et al, 2001;Tanaka and Nakaoka, 2004). However, possible future rises in sea levels threaten to drown or inundate coral reefs and islands (Leatherman, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…This study was conducted at Shiraho on Ishigaki Island in the Ryukyu Islands group, southwestern Japan (24°21' N, 124°15' E; see Tanaka & Nakaoka 2004 for more detailed information on the study site). Sampling and experiments were performed on 2 occasions (July 2001 andFebruary 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, depth distributions vary among species, leading to specific zonation patterns from intertidal to subtidal areas (Mukai et al 1987, Lee Long et al 1993, Björk et al 1999, De Troch et al 2001, Tanaka & Nakaoka 2004, Tanaka & Kayanne 2007. For subtidal seagrass beds, light intensity is a major factor determining species' depth distributions (Duarte 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged periods of high barometric pressure and calm seas can push the sea level below the Mean Low Water Level (MLWL), exposing sessile organisms to air for long periods. Such conditions may affect the physiology (Silva et al 2005) and growth of organisms (Davison et al 1993, Tanaka & Nakaoka 2004, Dethier et al 2005, their tolerance to the impact of waves (Haring et al 2002) and grazing (Buschmann 1990, Harley 2003. In contrast, waves reduce drying out of intertidal organisms during low tides and can have positive effects on transport of nutrient particles to filter-feeders (Hawkins & Jones 1992).…”
Section: Introductionmentioning
confidence: 99%